Increased brain radioactivity by intranasal 32P-labeled siRNA dendriplexes within in situ-forming mucoadhesive gels - Pérez, Ana Paula (2012)
Background: Molecules taken up by olfactory and trigeminal nerve neurons directly access the brain by the nose-to-brain pathway. In situ-forming mucoadhesive gels would increase the residence time of intranasal material, favoring the nose-to-brain delivery. In this first approach, brain radioactivity after intranasal administration of 32P-small interference RNA (siRNA) complexed with poly(amidoamine) G7 dendrimers (siRNA dendriplexes) within in situ-forming mucoadhesive gels, was determined. Materials: 32P-siRNA dendriplexes were incorporated into in situ-forming mucoadhesive gels prepared by blending thermosensitive poloxamer (23% w/w) with mucoadhesive chitosan (1% w/w, PxChi) or carbopol (0.25% w/w, PxBCP). Rheological properties, radiolabel release profile, and local toxicity in rat nasal mucosa were determined. The best-suited formulation was intranasally administered to rats, and blood absorption and brain distribution of radioactivity were measured. Results: The gelation temperature of both formulations was 23°C. The PxChi liquid showed non-Newtonian pseudoplastic behavior of high consistency and difficult manipulation, and the gel retained 100% of radiolabel after 150 minutes. The PxCBP liquid showed a Newtonian behavior of low viscosity and easy manipulation, while in the gel phase showed apparent viscosity similar to that of the mucus but higher than that of aqueous solution. The gel released 35% of radiolabel and the released material showed silencing activity in vitro. Three intranasal doses of dendriplexes in PxCBP gel did not damage the rat nasal mucosa. A combination of 32P-siRNA complexation with dendrimers, incorporation of the dendriplexes into PxCBP gel, and administration of two intranasal doses was necessary to achieve higher brain radioactivity than that achieved by intravenous dendriplexes or intranasal naked siRNA. Conclusion: The increased radioactivity within the olfactory bulb suggested that the combination above mentioned favored the mediation of a direct brain delivery.